Cochlear implantation in chronic demyelinating inflammatory polyneuropathy†. (4th March 2017) - Mowry, Sarah E.; King, Sarah
Abstract : Objective : To describe a case of chronic inflammatory demyelinating polyneuropathy (CDIP) with bilateral sudden sensorineural hearing loss who subsequently benefited from unilateral cochlear implantation. Methods : case history review and review of the literature for the terms CDIP, hearing loss, cochleovestibular dysfunction, and cochlear implantation. Results : A 49-year-old woman presented with bilateral rapidly progressive sensorineural hearing loss (SNHL) 1 month after an upper respiratory tract infection. Hearing loss was not responsive to high-dose steroids and there were no other laboratory abnormalities or physical findings. Within 1 month, she developed ascending motor palsy, requiring long-term ventilator support. This neurologic condition was diagnosed as CDIP and she was successfully treated with plasmapheresis and intravenous immunoglobulin. Her hearing never recovered. At the time of cochlear implant, she had no response at the limits of the audiometer and obtained 0% on AzBio testing. No ABR could be recorded preoperatively. She underwent uneventful cochlear implantation with a perimodilar electrode. One year after activation, she had a PTA of 20 dB and 40% on AzBio sentence testing. Her eABR demonstrated a neuropathy pattern. Only two other cases of CDIP associated with dysfunction of the eighth nerve have been described, and neither had documented profound hearing loss. Conclusions : Severe SNHL associated with CDIP is rare. Although this patient has good access to sound, speech discrimination is poor at 1-year post implantation. This outcome may be due to incomplete recovery of myelination of the eighth nerve. Other possibilities include loss of peripheral nerve fibers due to the initial viral upper respiratory infection, which may lead to less neural substrate to stimulate.